2000
DOI: 10.1046/j.1365-2036.2000.014s1082.x
|View full text |Cite
|
Sign up to set email alerts
|

Is autonomic dysfunction a necessary condition for chronic peptic ulcer formation?

Abstract: Background:The relationship between 1/f¯uctuation of the heart rate variability and Helicobacter pylori infection was evaluated, in order to clarify whether autonomic nervous dysfunction is a necessary condition for chronic peptic ulcer formation. Methods: The subjects were 11 patients with recurrent chronic peptic ulcer and 20 age-matched normal subjects. Holter ECGs were recorded over 24 h, and the 1/f ±x¯u ctuation of the heart rate was computed. The 1/f ±x¯u ctuation of the heart rate is a novel index of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…Testoni et al [68] also showed a significantly greater prevalence of H. pylori infection in patients without evidence of gastric phase Ⅲ of the migrating motor complex. Collectively, these data indicate that the coexistence of ANS dysfunction and H. pylori infection is a necessary condition for H. pylori invasion, as well as for chronic gastritis and peptic ulcer formation [6,14,15,21,22,29,[35][36][37][38][39] (but see Chang et al [69] ).…”
Section: Role Of the Brain-gut Axis In Acute H Pylori Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Testoni et al [68] also showed a significantly greater prevalence of H. pylori infection in patients without evidence of gastric phase Ⅲ of the migrating motor complex. Collectively, these data indicate that the coexistence of ANS dysfunction and H. pylori infection is a necessary condition for H. pylori invasion, as well as for chronic gastritis and peptic ulcer formation [6,14,15,21,22,29,[35][36][37][38][39] (but see Chang et al [69] ).…”
Section: Role Of the Brain-gut Axis In Acute H Pylori Infectionmentioning
confidence: 99%
“…Lugon et al [122] reported blunted sympathetic reactivity and an exacerbated vagal response to feeding in H. pyloripositive subjects. However, Katoh et al [36] have shown that H. pylori eradication in duodenal ulcer patients does not change nocturnal sympatheticotonia or parasympatheticotonia, which may be the cause for persistently increased gastric acid secretion, gastric mucosal vasoconstriction and ulcer recurrence [38,121] , though the time course between eradication and ANS evaluation may have been too short to reveal statistically significant differences. Indeed, Stanghellini et al [123] suggest there is long-term recovery of H. pylori-induced neuroplastic changes in the ANS and highlight the importance of an incomplete resolution of gastritis and the presence of a persistent production of inflammatory mediators even after successful H. pylori eradication.…”
Section: H Pylori and Ans Activitymentioning
confidence: 99%
See 3 more Smart Citations